Xylem embolism in leaves does not occur with open stomata evidence from direct observations using the optical visualization technique - Creek, Danielle (Journal of experimental botany, 2020)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.